UJI VALIDITAS DAN RELIABILITAS ALAT UKUR KECANDUAN GAME ONLINE PADA MAHASISWA PERGURUAN TINGGI SWASTA DI BEKASI - Chester Carlos Sihombing, Barry (Berajah Journal, 2025)
The phenomenon of online game addiction among students at private universities in Bekasi is now a real challenge that must be addressed immediately. Many students admit to having difficulty managing their gaming time, even to the point of sacrificing their coursework and class attendance. This study aims to describe online game addiction among students at the STIAMI Institute, Bekasi campus, who are members of an online game community. This study aims to test the validity and reliability of an online game addiction measurement tool among students at the STIAMI Institute, Bekasi campus, who are members of an online game community. This study uses a quantitative descriptive method where primary data is collected through the distribution of questionnaires to 113 respondents, all of whom are online game addicts who are members of a community called Warung Babeh.